B345 Intensity of acute postoperative pain after alteration of multimodal analgesia protocol. (11th August 2022) - Lebedeva, V; Golubovska, I; Tanaino, R; Miscuks, A
Abstract : Background and Aims: Multimodal analgetic approach uses a combination of different classes of analgesic, opioids, adjuvants, loco-regional invasive techniques. Optimization of the multimodal approach is essential for better postoperative pain outcomes. The aim of study was to analyse postoperative pain in years between 2018 and 2021 after a modification of multimodal analgesia protocol. Methods: A retrospective cross-sectional study of patients who underwent different orthopedic surgical procedures. Pain intensity was evaluated by using a Visual Analogue Scale (VAS). All patients were asked about pain four times a day. A total of 376 patients were included in the study. Results: On the operation day higher median of mean pain was after knee replacement 4.0 (IQR: 2.5–5.5) and the same after spine surgery, lower median of mean pain was after rotator surgery 2.0 (IQR: 1.0–4.4). On the first day after surgery higher median of mean pain was after knee replacement 4.0 (IQR: 2.0–5.4) humerus osteosynthesis 4.0 (IQR: 2.3–5.4) and rotator surgery 4.0 (IQR: 2.0–5.4), lower median of mean pain was after hip replacement 2.0 (IQR: 1.1–3.0) and revision surgery 2.0 (IQR: 1.0–4.3) Lower median of mean pain on the second postoperative day was after hip replacement 0.5 (IQR: 0–2.0) and higher median of mean pain after knee replacement 4.0 (IQR: 2.0–5.5). Conclusions: The results show that the leading position in higher pain scores remains after knee replacement surgery. The lowest pain scores were after hip replacement, then rotator, and revision surgeries.